Antonio Rosmini on Law and Its Implications for Fundamental Rights - Swartz, Nico P (Advances in Social Sciences Research Journal, 2016)
According to Rosmini, the simple interpretation of law and implication of fundamental rights is necessary in civil society in order to establish justice. The individual serves as a starting point for the perception of fundamental rights. The law is an objective entity outside man. Man can only understand law via acts of volition of the intellect. Rosmini alleges that law serves as transition for man to reach perfection. In order for man to achieve perfection, he must comply with the laws in the civil society. Law is therefore a creation by God for the maintenance of justice and order in civil society. The upholding of the law connotes that man must have honest characteristics and know how to pursue good. The human instinct for perfection serves as motive for man to do good. According to this idea, the principle of law can thus be inferred from God. Man will always be obliged by law to act morally good in civil society.